2006
DOI: 10.1161/01.str.0000226993.88307.ff
|View full text |Cite
|
Sign up to set email alerts
|

Large Subcortical Infarcts

Abstract: Background and Purpose-In this study we compared risk factors, clinical features, and stroke recurrence in a large series of patients with large subcortical, cortical, or small deep infarcts. Methods-Patients with a transient or minor ischemic attack (modified Rankin Scale grade of Յ3) who had a single relevant supratentorial infarct of presumed noncardioembolic origin on CT were classified as suffering from a large subcortical (nϭ120), small deep (nϭ324), or cortical (nϭ211)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…[97][98][99][100][101][102][103][104] Cardioembolic stroke may be expected to have a higher likelihood of CHD events, perhaps related to the underlying presence of cardiac disease. The European Atrial Fibrillation Trial (EAFT) provides some evidence on this point, although the study did not report results for MI alone as an outcome.…”
Section: Importance Of Stroke Subtypes/special Situations Stroke Hetementioning
confidence: 99%
“…[97][98][99][100][101][102][103][104] Cardioembolic stroke may be expected to have a higher likelihood of CHD events, perhaps related to the underlying presence of cardiac disease. The European Atrial Fibrillation Trial (EAFT) provides some evidence on this point, although the study did not report results for MI alone as an outcome.…”
Section: Importance Of Stroke Subtypes/special Situations Stroke Hetementioning
confidence: 99%
“…Infarctions with diameters ≥15 mm located in deep penetrating arteries are called giant lacunae or LSCI [1, 2]. In clinical practice, patients with LSCI who present with progressive stroke conditions (stroke-in-evolution) in the acute phase are encountered frequently.…”
Section: Introductionmentioning
confidence: 99%
“…9,35 A Dutch trial reviewed patients with LSI of presumed noncardioembolic origin on CT. 9 Clinical features and risk factor profiles were similar in patients with LSI as compared with those with LIs or CIs. Clinical outcomes were not assessed, but stroke recurrence rates were similar.…”
Section: Downloaded Frommentioning
confidence: 99%
“…[3][4][5][6][7][8] One exception was a Dutch trial, where no differences were found regarding clinical features or risk factor profiles in patients with LSIs as compared with lacunar (LIs) or cortical infarctions (CIs) diagnosed with computed tomography (CT). 9 Because several patients with stroke are without sign of infarction on CT, stroke localization and classification may be inaccurate.…”
mentioning
confidence: 99%